2021
DOI: 10.11604/pamj.2021.39.106.23667
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and decision making towards prenatal testing among antenatal clinic attendees in Lagos University Teaching Hospital: an institution-based cross-sectional study

Abstract: Introduction in Africa, genetic diseases and congenital anomalies remain a significant source of morbidity and mortality. Existing data suggests a gap in the use of prenatal tests among pregnant women to better inform decision making. We examined relationships of socio-demographic factors with willingness to terminate affected pregnancies, and the use of, knowledge of, and attitudes towards prenatal screening/diagnostic tests. Methods this was a cross-sectional descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, our findings align with those from Turkey, where a study of 274 women reported a similar proportion (34.3%) with adequate knowledge [ 11 ]. In contrast, studies conducted in Nigeria reported lower percentages, with one study among 417 women indicating 18.5% and another among 422 women showing 17.1% [ 12 , 13 ]. Conversely, a study in Greece among 354 women found that 50.8% had adequate knowledge [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our findings align with those from Turkey, where a study of 274 women reported a similar proportion (34.3%) with adequate knowledge [ 11 ]. In contrast, studies conducted in Nigeria reported lower percentages, with one study among 417 women indicating 18.5% and another among 422 women showing 17.1% [ 12 , 13 ]. Conversely, a study in Greece among 354 women found that 50.8% had adequate knowledge [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from various studies conducted in different regions provide valuable insights into the acceptability of prenatal screening tests among pregnant women. In Lagos, a significant majority (81.3%) expressed a belief in the necessity of offering these tests to all expectant mothers, with a substantial proportion (75.1%) indicating a willingness to pursue further diagnostic testing if initial screening results raised concerns [ 15 ]. Similarly, studies in Greece, Ibadan, and Sokoto, and reported high levels of acceptability, with percentages ranging from 68% to 95.2% [ 13 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability scores were positively correlated with the educational status of the participants [ 15 , 16 , 21 ]. In our study, educational attainment emerged as a significant predictor of acceptability, with women holding a university degree demonstrating greater acceptance of prenatal screening tests.…”
Section: Discussionmentioning
confidence: 99%